L’Europe audiovisuelleSur l’imaginaire social de Visions of Europe (2004) - Raphaël Szöllösy (Mise au Point)
Visions of Europe is a collective movie, produced by Zentropa, that was made for the enlargement of the EU to 25 member states, on May 1st, 2004. The study of the film helps us to consider cinema as a sensor for « social imaginations »: as an apparatus, it produces and receives signs, symbols, figures, desires or wishes, and it could lead to considering these imaginations as symptoms of the social world. The 25 short movies from Visions of Europe problematize our times: can we think about the European political community in terms of solidarity instead of competition?